KEPASTIAN HUKUM TERHADAP MOBIL BERTEKNOLOGI AUTO PILOT DITINJAU DARI PERSPEKTIF HUKUM LALU LINTAS JALAN DI INDONESIA - Febby Mirza Juliansyah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
With the development of science and technology today, it triggers car manufacturers to create cars that can provide a sense of security and comfort to its users. They attract the interest of consumers by offering quality cars equipped with sophisticated computerized systems that make it easy and provide a sense of security for the driver. Apart from electric cars, what is currently becoming a trend in the automotive world are cars with autopilot features. Autonomous vehicles with artificial intelligence, are now not only prototypes, but can be found in several countries. This of course creates a debate between manufacturers, policy makers and users of these vehicles. In addition, there are many pros and cons to autonomous vehicles in various circles. The presence of autonomous vehicles is unavoidable, even though there are still many shortcomings, but manufacturers are always trying to improve it and offer the most advanced features applied to these vehicles, one of which is autopilot technology that replaces the role of the human driver. However, the presence of autopilot technology in this vehicle creates new problems in the field of law enforcement. With regard to traffic accidents due to errors in the navigation system or autopilot sensors, what kind of rules will be imposed, and to which who is the legal liability imposed? Therefore, in this research, the author tries to find conformity in the field of law enforcement and certainty for autonomous vehicles with artificial intelligence, in the event of an accident in the jurisdiction of the Republic of Indonesia